Polarization-resolved second harmonic microscopy of skeletal muscle in sepsis - Dubreuil, Matthieu (Biomed Opt Express, 2018)
Polarization-resolved second harmonic generation (P-SHG) microscopy is able to probe the sub-micrometer structural organization of myosin filaments within skeletal muscle. In this study, P-SHG microscopy was used to analyze the structural consequences of sepsis, which is the main cause of the critical illness polyneuromyopathy (CIPNM). Experiments conducted on two populations of rats demonstrated a significant difference of the anisotropy parameter between healthy and septic groups, indicating that P-SHG microscopy is promising for the diagnosis of CIPNM. The difference, which can be attributed to a change of myosin conformation at the sub-sarcomere scale, cannot be evidenced by classical SHG imaging.